Sewage Sludge-Derived Biochar for the Adsorptive Removal of Wastewater Pollutants: A Critical Review - Sepúlveda-Ortiz, P; Sepúlveda-Ortiz, P (Elsevier Ltd, 2022)
The production of biochar from sewage sludge pyrolysis is a promising approach to transform the waste resultant from wastewater treatment plants (WWTPs) to a potential adsorbent. The current review provides an up-to-date review regarding important aspects of sewage sludge pyrolysis, highlighting the process that results major solid fraction (biochar), as high-value product. Further, the physio-chemical characteristics of sewage-sludge derived biochar such as the elemental composition, specific surface area, pore size and volume, the functional groups, surface morphology and heavy metal content are discussed. Recent progress on adsorption of metals, emerging pollutants, dyes, nutrients and oil are discussed and the results are examined. The sewage sludge-derived biochar is a promising material that can make significant contributions on pollutants removal from water by adsorption and additional benefit of the management of huge volume of sewage. Considering all these aspects, this field of research still needs more attention from the researchers in the direction of the technological features and sustainability aspects. © 2021 Elsevier Ltd